If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 6z + -1(3z + -6) + (7 + -8z) Reorder the terms: 0 = 6z + -1(-6 + 3z) + (7 + -8z) 0 = 6z + (-6 * -1 + 3z * -1) + (7 + -8z) 0 = 6z + (6 + -3z) + (7 + -8z) Remove parenthesis around (7 + -8z) 0 = 6z + 6 + -3z + 7 + -8z Reorder the terms: 0 = 6 + 7 + 6z + -3z + -8z Combine like terms: 6 + 7 = 13 0 = 13 + 6z + -3z + -8z Combine like terms: 6z + -3z = 3z 0 = 13 + 3z + -8z Combine like terms: 3z + -8z = -5z 0 = 13 + -5z Solving 0 = 13 + -5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '5z' to each side of the equation. 0 + 5z = 13 + -5z + 5z Remove the zero: 5z = 13 + -5z + 5z Combine like terms: -5z + 5z = 0 5z = 13 + 0 5z = 13 Divide each side by '5'. z = 2.6 Simplifying z = 2.6
| 15=3x-6x-3 | | 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 | | G(x)=8sin(5x^6) | | 6y^2+8y-8y-12= | | k^2+12k=-35 | | 2x^3-2x^2+7x-40=0 | | 9d+d-d+2-3d=0 | | 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 | | 2x+8+2x=10+2x+12 | | 1.2+y=-8 | | 4x-5=6x-13 | | 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 | | 2x+y-3x+4y-6+5y= | | 1/3(2x+9)=2/3x+3 | | 5x+20=15+10x | | a-16=2(3-a) | | 9y=18x-54 | | 2p+9-8p=3p-18 | | 3(x+2)=2(x+1)-5 |